Special Manifestations of Spoken Language in Bahr al-Ansāb (a Book about the Family of Ahmad-e Jām-e Zhende Pil) - Mahmood Nadimi Harandi (مطالعات زبانی و بلاغی)
Bahr al-Ansāb is a book in Persian language about the family of Ahmad-e Jām-e zhende Pil, which was written by Muhammad Hakim-e Jāmi in 1034 AH (1656 AD). The book is considered an authentic source about the members of Sheikh Ahmad-e Jām's family, their lives and social and official status, in the second half of the 10th century and the first half of the 11th century. It also provides information about the familial links, several male and females names common in that era, as well as geographical names related to the area of Jam. In many places, the prose of Bahr al-Ansāb is close to spoken language and is written in a colloquial tone. In fact, its author was influenced by folk culture and accepted the style and general tendency of the society in using spoken language in writing. In the present research, the special manifestations of the spoken language of Bahr al-Ansāb have been investigated at three phonetic, lexical, and syntactic levels in order to obtain an example of the spoken language of Khorāsān during the Safavid era.